Repeated acceleration ability (RAA): a new concept with reference to top-level field and assistant soccer referees - Barbero-Alvarez, J. C.; Boullosa, D.; Nakamura, F. Y.; Andrin, G.; Weston, M. (Asian Journal of Sports Medicine, 2014)
Purpose: To perform an exploratory characterization of repeated sprint sequences (RSS) and repeated acceleration sequences (RAS) in top level soccer referees.